KESIAPAN PELABUHAN PERIKANAN PANTAI (PPP) LEMPASING DALAM MENDUKUNG PENGEMBANGAN PELABUHAN BERWAWASAN LINGKUNGAN (ECOPORT) - Ermawati, Mia (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
One of the potentials in supporting the fisheries sector in Lampung Province is the Lempasing Coastal Fishing Port (PPP Lempasing). The PPP Lempasing port plays a role in controlling the economy, especially in capture fisheries, for the surrounding community. In order to maintain the sustainability of the Lempasing fishing port, it is necessary to implement a concept called Ecoport. Ecoport is an idea that emphasizes environmentally conscious port management. The purpose of this research is to realize PPP Lempasing as an Ecoport by integrating fishing port activities based on sustainable principles that preserve marine ecosystems and local communities. This research uses qualitative descriptive analysis to comprehensively describe the aspects of developing an environmentally conscious fishing port. Data collection in this research is carried out through primary surveys and secondary surveys. Based on the analysis results, it is shown that in realizing the development of an environmentally friendly port (Ecoport), it can be done through the optimization of the location of coastal fishing ports, the use of renewable energy, involvement of local communities, and cooperation with external parties. Additionally, supervision of fish populations and prevention of overfishing should be conducted, and the local community can be educated about environmental pollution, technological innovations in fisheries, fishery product processing, and expanding fishery markets.